O trabalho docente do professor de Educação Física e suas relações sociais - Luiz Alberto de Souza Ferreira Pinto (2013)
This thesis set out to research, study and discuss the Teaching Work of Physical Education teacher, identifying what is the contribution that their Work adds to Teacher Education Process in school. This study/survey was based, on a qualitative-quantitative methodological approach, however, received no statistical treatment, only, a percentage analysis. Thus, data collection used both questionnaires (quantifying responses), for the systematic observations. Thus, the research set up, an Exploratory Study when it proposed methodological develop strategies to reach the goal of Work. The AXIS RESEARCH were made after an exhausting journey of confrontation and/or crossing issues between managers and teachers that by waging a dialogue with the theory, configured the central chapters (2 and 3), allowing within each, walking for preparing the end conclusions. The main references are used Bracht (1992, 1997 and 2007), Mattos (1994), Mattos and Neira (2000), Daolio (2003, 2006 and 2007) and Pinto (2007), all cited authors are professors at area Physical Education. We tried to, too, several authors in Sociology explanations of the behaviors, attitudes, actions, reactions observable Physical Education teachers inthe schools surveyed. Among other authors was with Esteve (1999) who caught up,important dialogue about "malaise" teacher. The introduction included the research proposal and explained the research method adopted and its particularities. The theoretical and empirical discussion was then divided into two parts by thesis analyzes: in chapter 2, first AXIS RESEARCH, the Pedagogical Practices of the PhysicalEducation teacher were discussed in order to show that the teacher's commitment to quality regency lesson is that the main contribution in the Education Process. Chapter 3 begins, with a brief historical overview. Goes on to discuss the role ofthe teacher outside the classroom, but, also discusses some more physical education, as a school subject. As a second AXIS RESEARCH, that chapter 3, the Teaching Work ofPhysical Education teacher was subdivided into Working with Interactive Collective School, and Interactive Work with Members of the School Community. Also, this second AXIS RESEARCH relies sure that Education and jobs are school staff. The conclusions empties into, two sequences of Frames Syntheses, in which it is possible to visualize how the Teaching Work, is configured to forward data from both segments surveyed. Therefore, the conclusion points to an insufficient Teaching Work of Physical Education teacher, however, is something that can not be evaluated outside of the context of the various occurrences in the school environment, and not outside the historical fact of initial deficit of any teacher. References, appendices and glossary take place at the end of the Work.